Diarylmaleic anhydrides: unusual organic luminescence, multi-stimuli response and photochromism. Issue 8 (10th February 2017) - Mei, Xiaofei; Wang, Jingwei; Zhou, Zhonggao; Wu, Shiyi; Huang, Limei; Lin, Zhenghuan; Ling, Qidan
Abstract : Novel maleic anhydrides symmetrically substituted by two aromatic rings exhibit distinct emission behaviours: aggregation-caused quenching (ACQ), aggregation-induced emission (AIE), and dual-state emission (DSE) in both solution and the solid state. Appropriate modifications were made to turn ACQ/AIE into DSE and realize full-color DSE. Abstract : Diarylmaleic anhydride derivatives containing benzene (BPMA ), thiophene (BTMA ) and indole (BIMA ) exhibit diverse and distinct fluorescence: aggregation-caused quenching (ACQ) of red emission ofBIMA, blue aggregation-induced emission (AIE) ofBPMA, and green dual-state emission (DSE) ofBTMA in both solution and the solid state. Theoretical calculation and crystal structure analysis indicate that intramolecular and intermolecular interactions are responsible for their different emission behavior. A series of DSE-active molecules with full-color emission could be developed for the first time, through modification of the structures ofBPMA andBIMA . Interestingly, BTMA andBPMA display multi-stimuli-responsive luminescence with a high-contrast (Δ λ em > 100 nm) and an unusual photochromic phenomenon in dichloromethane, which were utilized to construct rewritable data storage and mimic molecular logic operation (4-to-2 encoder and 1 : 2 demultiplexer), respectively.